Determination of selected anions and selected water parameters of Jalaur River in Passi City. Morwena Jane V. Solivio. - Solivio, Morwena Jane V.
Water samples were collected from 5 sites to assess the water quality of the Jalaur River in Passi City and its suitability for the purpose based on the classification assigned by the Department of environment and Natural Resources (DENR)., The average Dissolved Oxygen in Jalaur River is 5.68 mg/L. It is low but is still within the limit for "Class C" waters set by the DENR, which is 5.0 mg/L. The average pH value is 5.79 and is not within the standard pH range of 6.5-8.8 set by the DENR for "Class C" waters. The average Total Solid is 284 mg/L and is within the limit for "Class C" waters, which is 2,000 mg/L. The average concentration of Nitrite in Jalaur River is 7.31 ppb and is within the limit of 10 ppm set by the DENR for "Class C" waters. The concentration of Nitrates on the other hand, which is 39.9 ppb, is within the safe limit for nitrite in water, which is 45 ppm set by the US Public Health Service. The average concentration of Total Phosphorus is 0.153 ppm. It is above the recommended limit set by the US EPA, which 0.1 ppm, however, it still within the limit set by the DENR for "Class C" waters, which is 0.4 ppm. The DENR did not set any criteria for Sulfate and Chloride. The average Sulfate concentration is 23.4 ppm. It is within the limit set for domestic water supply, which is 250ppm. The average concentration of Chloride is 5.00 mg/L and is below the maximum contaminant level set by the World Health Organization (WHO), which is 250 mg/L and the criteria for protection of aquatic life which requires levels less than 600 mg/L for chronic (long term) exposure and 1,200 mg/L for short term exposure. The Jalaur River is able to comply with the criteria for "Class C" waters for all anions and all parameters except for a slightly lower pH than the set limit.